Estudos sobre a psicopatia - Peres, Kenia (2008)
This thesis is the result of the extensive research in psychopath, a psychopathologic phenomenon so common in our society nowadays; however, it s very little explored, maybe because of the difficult technique in handling with these patients. The interest in understanding the psychodynamics of these people matches my Professional development, as a researcher and as a psychologist. In this work I have used, besides the bibliography research of the psychoanalytic theory about the issue, studies of real cases and more stores with the intention of enrich such investigation. The objective of this study is besides of the thinking exercise to understand the psychopathic person, to create resources to develop ways to handle with these patients and, consequently diminish the psychic suffering of them, of the ones who are near them and all society. The methodology used in this work is psychoanalysis, as a theory of the psyche, investigative method of the unconscious and therapeutic technique